Thermomagnesium: A By-Product of Ni Ore Mining as a Clean Fertilizer Source for Maize - Bossolani, Joao William [UNESP]; Moretti, Luiz Gustavo [UNESP]; Portugal, Jose Roberto [UNESP]; Rossi, Ricardo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Mdpi, 2021)
This study explores whether Thermomagnesium (TM), a by-product of Ni ore mining, is an efficient fertilizer for maize. The effects of TM on soil pH, the supply of Si and Mg to the soil and plants, carbohydrate metabolism, grain filling, and yield were assessed in two simultaneous experiments performed in greenhouse conditions. Five TM doses were applied to two soil textures-clayey (0, 55, 273, 709, and 2018 mg kg(-1)) and sandy (0, 293, 410, 645, and 1260 mg kg(-1)). In general, the best results in soil and maize plants occurred at the highest TM dose for both soil textures (clayey 2018 mg kg(-1) and sandy 1260 mg kg(-1)). The results demonstrated that in both soils, the concentrations of Mg and Si in the maize leaves increased with the dose of TM, similarly to that which occurred in the soil. Interestingly, in clayey soil, the soil pH increased linearly, whereas in sandy soil, the pH reached its maximum value between the two largest TM doses. The concentration of reducing sugars increased at the highest TM dose, whereas the concentrations of sucrose and starch decreased. The enhancement of carbohydrate partitioning led to higher maize growth, grain filling, and yield. Overall, the results clearly demonstrate that TM is a sustainable alternative fertilizer for maize and can be used for countless other crops and soil classifications, thus providing a suitable destination for this by-product of Ni ore mining.
Keywords: Zea mays (L); mining waste; magnesium silicate; carbohydrate partitioning; grain filling